Three centers experience with device closure of congenital Gerbode‐type perimembranous ventricular septal defects. Issue 9 (30th June 2022) - Haddad, Raymond N.; Boudjemline, Younes; Combes, Nicolas; Hadeed, Khaled; Karsenty, Clement; Saliba, Zakhia
Abstract: Objectives: We aim to evaluate our experience with interventional closure of Gerbode‐type perimembranous ventricular septal defects (pmVSDs). Methods: We performed three‐center retrospective data review of patients with congenital indirect Gerbode‐type pmVSDs treated percutaneously between August 2017 and May 2021. Standard safety and latest follow‐up outcomes were assessed. Results: Ten patients (six females) were identified with a median age of 6.8 years (range: 2.5–54) and a median weight of 26.5 kg (range: 12–88). The median left ventricular defect size was 10 mm (range: 3–15.5). On baseline ultrasound, 6 patients had absent subaortic rim , 6 patients had trivial aortic regurgitation, and 3 patients had tear‐drop‐type (small) aortic cusp prolapse. The tricuspid regurgitation was graded II ( n = 5) and III ( n = 5). Five Lifetech Konar‐Multifunctional occluders, four Amplatzer duct occluders II and one Amplatzer duct occluder I were implanted. The median fluoroscopy time was 10.4 min (range: 4.3–20.2). Pre‐existing aortic regurgitations remained identical. One new aortic regurgitation was identified before discharge and remained trivial after 48 months of follow‐up. No heart block or tricuspid stenosis was observed on a median follow‐up of 17 months (range: 3–48). All patients are symptom‐free with complete shunt closure and significant regression or resolution of tricuspid regurgitation. Conclusions: Despite anatomical challenges, interventional closure of congenital indirect Gerbode‐type pmVSD appears to be feasible, safe, and most importantly clinically effective using different commercially available devices. Amplatzer duct occluder II and Lifetech Konar‐Multifunctional occluder offer interesting specifications to retrogradely target this specific defect with success.